MICROWAVE SYNTHESIS OF SILVER NANOPARTICLES BY POLYOL METHOD AND TESTING THEIR SYNERGISTIC ANTIBACTERIAL ACTIVITY IN THE PRESENCE OF VANCOMYCIN - D, Malathy; Revathi, Meyappan; M, Letticia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to prepare silver nanoparticles (AgNPs) and nanorods using polyol under microwave heating method. Methods: The synthesized nanoparticles were characterized using UV-visible, infrared spectral studies (Fourier-transform infrared [FTIR]), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Finally, the antibacterial activity of polyethylene glycol (PEG) protected AgNPs, against a series of Gram-positive and Gram-negative bacteria, was studied. Results: From UV-visible spectroscopy studies, the growth rate of AgNPs was confirmed by measuring the change in absorbance of plasmon peak shape at different time intervals. FTIR spectroscopy studies showed the changes in the metal and the capping agents. SEM and TEM images revealed that very stable colloidal solutions of AgNPs with almost spherical and rod shape along with high monodispersity can be obtained with PEG protected AgNPs. Finally, the antibacterial activity of PEG protected AgNPs was investigated, which showed a synergistic role for the AgNPs along with vancomycin. Conclusion: Uniform and stable polymer protected AgNPs were synthesized using ethylene glycol, triethylene glycol, and PEG as reducing agent in the presence of polyvinylpyrrolidone.